Computational fluid dynamics modelling of an entire synchronous generator for improved thermal management - Connor, Peter H.; Pickering, S.J.; Gerada, C.; Eastwick, Carol; Micallef, Christopher; Tighe, Chris (Institution of Engineering and Technology, 2013)
This study is the first in a series dedicated to investigating the airflow and thermal management of electrical machines. Owing to the temperature dependent resistive losses in the machine's windings, any improvement in cooling provides a direct reduction in losses and an increase in efficiency. This study focuses on the airflow which is intrinsically linked to the thermal behaviour of the machine as well as the windage power consumed to drive the air through the machine. A full computational fluid dynamics (CFD) model has been used to analyse the airflow around all major components of the machine. Results have been experimentally validated and investigated. At synchronous speed the experimentally tested mass flow rate and windage torque were under predicted by 4% and 7%, respectively, by the CFD. A break-down of torque by component shows that the fan consumes approximately 87% of the windage torque.